Performan Reproduksi Sapi PO pada Dataran Rendah dan Dataran Tinggi di Provinsi Jambi - Iskandar, Iskandar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The research was conducted to evaluate the reproductive performance of PO cattle on lowland and highland in Jambi Province.  Sekernan Regency (lowland) and Kayu Aro Regency (highland) were purposively chosen as  a  sample  of  two  different  area.  Data  were    analyzed using  Z-test.  The  number  of  cattle  reared  was relatively  similar  between  Sekernan  Regency  (1.98  heads)  and  Kayu  Aro  Regency  (2.02  heads). Reproductive  performance  of  PO  cattle  was  significantly  different  (P<0.01) between  two  areas    on  age  of puberty (Kayu Aro vs Sekernan : 672,76 d vs 823.44 d),  age of first mating ( 694.11 d vs 847.89 d). service period  (114.00  d  vs  162.45  d). Service  per  conception  in  Kayu  Aro  and  Sekernan  was  1.3  and  1.5 respectively. In conclusion, there were differences on reproductive performance of PO cattle between lowland and highland areas in Jambi Province.